Mitochondrial pseudogenes in the nuclear genome of Aedes aegypti mosquitoes: Implications for past and future population genetic studies - Hlaing T. (2014)
Background: Mitochondrial DNA (mtDNA) is widely used in population genetic and phylogenetic studies in animals. However, such studies can generate misleading results if the species concerned contain nuclear copies of mtDNA (Numts) as these may amplify in addition to, or even instead of, the authentic target mtDNA. The aim of this study was to determine if Numts are present in Aedes aegypti mosquitoes, to characterise any Numts detected, and to assess the utility of using mtDNA for population genetics studies in this species. Results: BLAST searches revealed large numbers of Numts in the Ae. aegypti nuclear genome on 146 supercontigs. Although the majority are short (80% < 300 bp), some Numts are almost full length mtDNA copies. These long Numts are not due to misassembly of the nuclear genome sequence as the Numt-nuclear genome junctions could be recovered by amplification and sequencing. Numt evolution appears to be a complex process in Ae. aegypti with ongoing genomic integration, fragmentation and mutation and the secondary movement of Numts within the nuclear genome. The PCR amplification of the putative mtDNA nicotinamide adenine dinucleotide dehydrogenase subunit 4 (ND4) gene from 166 Southeast Asian Ae. aegypti mosquitoes generated a network with two highly divergent lineages (clade 1 and clade 2). Approximately 15% of the ND4 sequences were a composite of those from each clade indicating Numt amplification in addition to, or instead of, mtDNA. Clade 1 was shown to be composed at least partially of Numts by the removal of clade 1-specific bases from composite sequences following enrichment of the mtDNA. It is possible that all the clade 1 sequences in the network were Numts since the clade 2 sequences correspond to the known mitochondrial genome sequence and since all the individuals that produced clade 1 sequences were also found to contain clade 2 mtDNA-like sequences using clade 2-specific primers. However, either or both sets of clade sequences could have Numts since the BLAST searches revealed two long Numts that match clade 2 and one long Numt that matches clade 1. The substantial numbers of mutations in cloned ND4 PCR products also suggest there are both recently-derived clade 1 and clade 2 Numt sequences. Conclusion: We conclude that Numts are prevalent in Ae. aegypti and that it is difficult to distinguish mtDNA sequences due to the presence of recently formed Numts. Given this, future population genetic or phylogenetic studies in Ae. aegypti should use nuclear, rather than mtDNA, markers. © 2009 Hlaing et al; licensee BioMed Central Ltd.